State and local government : - Saffell, David C. (McGraw-Hill, 2005)
Beginning with the first edition in 1978, State and Local Government: Politics and Public Policies has been relied upon to present a concise, readable analysis of the structure and operation of state and local government. In this thoroughly updated edition, Saffell and Basehart emphasize how policies made in state capitals and city halls have an impact on our everyday lives, and they draw attention to ways in which students can become active participants in the affairs of their communities.